GENETIC STUDIES ON GROWTH RATES IN JAPANESE QUAILS (COTURNIX COTURNIX JAPONICA) - B . Punya kumari; B. Ramesh Gupta; M. Gnana Prakash; A. Rajasekhar Reddy; K. Sudhakar Reddy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The data on average daily gains (ADGs) during first, second, third, fourth, fifth to eight, nine to twelve, thirteen to sixteen and seventeen to twenty weeks of age in Black and Brown Japanese quails was analysed by least squares analysis for studying the effect of strains, generations, sex and hatches. The overall least squares means for ADGs at 1, 2, 3, 4, 5 to 8, 9 to 12, 13 to 16 and 17 to 20 weeks of age were 3.91, 5.78, 6.98, 6.36, 2.73, 0.55, 0.34 and 0.30 g, respectively. The effects of strain, sex and hatch was significant on ADGs at all ages except ADG 9-12, while the influence of generation was evident on ADGs at all ages. The birds of 7th generation exhibited highest average daily gains and sexual dimorphism was in favour of females. Low to high heritability estimates were obtained for ADGs at all ages in Black and Brown Japanese quails by half-sib as well as full sib methods. Moderate to high genetic correlations with positive direction were observed among the majority of the combinations, while low to medium correlations were noticed at phenotypic and environmental level with inconsistency in direction based on half sib analysis. The genetic correlations based on various components of variance (full sib analysis) were mostly moderate to highly positive for majority of the combinations in both Black and Brown Japanese quails, while most of the phenotypic correlations were low to medium and inconsistent in direction.